2018
DOI: 10.1002/mpr.1718
|View full text |Cite
|
Sign up to set email alerts
|

Handwriting assessment to distinguish comorbid learning difficulties from attention deficit hyperactivity disorder in Chinese adolescents: A case–control study

Abstract: Clinicians should be aware of the fundamental difference between the 2 disorders and make good use of handwriting assessment as a reference to deliver effective therapies and trainings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 33 publications
(33 reference statements)
2
15
0
Order By: Relevance
“…It is supported by the present study wherein there was no significant difference between the girls with and without ADHD, as females with ADHD are known to have fewer hyperactive/impulsive symptoms and more inattentive symptoms than males [19]. Other studies suggested that children with ADHD have a less appropriate speed of execution and more motor difficulties than children without ADHD [4, 20], but they did not distinguish the comorbid learning difficulties in ADHD that can cause lower writing speed [21]. Among the females, the handwriting of subjects with ADHD was never ascending compared to variable findings in the control group.…”
Section: Discussionsupporting
confidence: 45%
“…It is supported by the present study wherein there was no significant difference between the girls with and without ADHD, as females with ADHD are known to have fewer hyperactive/impulsive symptoms and more inattentive symptoms than males [19]. Other studies suggested that children with ADHD have a less appropriate speed of execution and more motor difficulties than children without ADHD [4, 20], but they did not distinguish the comorbid learning difficulties in ADHD that can cause lower writing speed [21]. Among the females, the handwriting of subjects with ADHD was never ascending compared to variable findings in the control group.…”
Section: Discussionsupporting
confidence: 45%
“…Other studies suggested that children with ADHD have a less appropriate speed of execution and more motor difficulties than children without ADHD [4,20], but they did not distinguish the comorbid learning difficulties in ADHD that can cause lower writing speed [21]. Among the females, the handwriting of subjects with ADHD was never ascending compared to variable findings in the control group.…”
Section: Discussionmentioning
confidence: 94%
“…Specific learning disorder may affect handwriting in a way that can be visually distinguished (Li-Tsang, Lau, Ho, & Leung, 2018). Symptoms of specific leaning disorder may include impairment in written expression such as difficulty with spelling, grammar, punctuation, and organization (American Psychiatric Association, 2013).…”
Section: Deep Learning and Specific Learning Disorder Diagnosismentioning
confidence: 99%
“…Symptoms of specific leaning disorder may include impairment in written expression such as difficulty with spelling, grammar, punctuation, and organization (American Psychiatric Association, 2013). Handwriting performance and sensorimotor skills may be affected by specific leaning disorder (Li-Tsang et al, 2018). Students with specific learning disorder write at slower speed, and with greater variation in written character size (Lam, Au, Leung , & Li-Tsang, 2011).…”
Section: Deep Learning and Specific Learning Disorder Diagnosismentioning
confidence: 99%